Theoretical considerations in urban low-income housing provision in the 90s - Abd. Mutalip, Abdullah (Kota Samarahan : Faculty of Social Sciences, Universiti Malaysia Sarawak, 2006)
The suffocating problem of urban housing faced by most countries today, especially those from the developing world, is likely to worsen in the future. Increasing population, unencumbered urbanisation, uncontrolled rural-urban migration (Smith, 1972) and unrealistic development standards (Ramachandran, 1972; McGee, 1979) will ensure the continuation and exarcebation of this demand for urban shelter. Characteristically, this problem has provoked different responses from housing academics. Peattie (1979) rose to the challenge by validly questioning or attempting to explain why such a problem exists. McGee (1979), on the other hand, denies the existence entirely and says, as does Ramachandran (I972), that the problem is there because of the application of some unacceptable world standards. On a completely opposite stance, Angel and Benjamin (1976) not only accept the existence of the problem but argue pessimistically that it can never be solved. Nevertheless, hypothetical or otherwise, this problem has generally elicited direct government intervention in the urban housing market, both in the form of the provider-based and support-based approaches, the results of which have incited more questions than answers (Sanoff, 1990). Bums and Grebler (1977) and the UNDP (1991) hinted that the provider-based response (Tipple, 1994) accounts for at least 20 percent of the total investment of a typical developing country, which can be equivalent to as much as 5 percent of its Gross Domestic Product. Despite such direct intervention involving enormous capital expenditure, the housing problem is little nearer to being solved. In simple market jargon, this failure is alluded to as the inability of the housing supply side of the housing market to meet the ever increasing housing demand. In political discourse, the failure and the huge amount invested insinuate not only the hidden expenditure objectives, but also the hypocritical desire to be seen to be doing something.